Erken başlangıçlı demansın görüldüğü erişkin tıp nöronal seroid lipofuksinoz olgusu - (:unkn) unknown (My University, 2006)
Bilimsel zemin: Erişkin yaşta başlayan nöronal seroid lipofuksinoz (Kufs Hastalığı) nadir görülen tanımlanması güç bir metabolik nörodejeneratif hastalıktır. Amaç: Psikiyatrik semptomlar ve ilerleyici bilişsel bozulması olan, miyelin kılıfında granüler osmiofilik depolanmalar ve Schwann hücre sitoplazmasında parmak izi profili gösterilen bir adult nöronal seroid lipofuksinoz olgusu tanımlanmaktadır. Tartışma: Erken başlangıçlı davranış değişikliği ve psikiyatrik semptomların da bulunduğu demans olgularında nöbet, motor bulguların ve aile anamnezinin varlığında ayırıcı tanıda nörodejeneratif bir metabolik hastalık olan Kufs hastalığı düşünülmelidir.

Scientific background: The adult onset form of neuronal ceroid lipofuscinosis (Kufs Disease) is a rare and poorly characterized entity of metabolic neurodegenerative disease. Objectives: We report a patient with psychiatric symptoms and progressive cognitive decline. We were able to show granular osmiophiiic deposits in myelin sheath and fingerprint profile in Schwann cell cytoplasm indicating the presence of adult neuronal ceroid lipofuscinosis. Discussion: Kufs disease should be considered in the differential diagnosis of early onset, progressive cognitive decline with psychiatric symptoms, seizures and motor disturbances especially in patients with positive family history.
Adult-onset neuronal ceroid lipofuscinosis presenting with early onset dementia
Keywords: Nörolojik Bilimler